2022
DOI: 10.3390/ijerph191811283
|View full text |Cite
|
Sign up to set email alerts
|

Post-Adoption Help-Seeking in Portugal: A Comprehensive Study on Parental Difficulties and Help-Seeking Behaviors and Perceptions

Abstract: Effective psychological parenting interventions delivered to adoptive parents may prevent serious adjustment difficulties and promote a healthy functioning; however, less is known about adoptive parents’ specific parental difficulties and help-seeking behaviors and perceptions, the understanding of which is deemed necessary to design well-informed interventions. This study aimed to describe parental difficulties, help-seeking behaviors, satisfaction with, and perceived barriers to seek, professional help, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Thus, while formal psychiatric diagnoses typically shape how statutory mental health services are organised, when inquiring of parental concerns, it may be helpful to use descriptions of problems and concerns rather than suggestions of frank psychiatric disorders. For example, a recent study of adopted parents in Portugal using descriptive rather than formal psychiatric terms reported a wide range of concerns, of similar form to those reported by birth families (Alves et al, 2022). Similar wide-ranging descriptions of concerns have also been found in UK samples (Meakings et al, 2018) and US samples (Houston & Kramer, 2008; Waid & Alewine, 2018).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, while formal psychiatric diagnoses typically shape how statutory mental health services are organised, when inquiring of parental concerns, it may be helpful to use descriptions of problems and concerns rather than suggestions of frank psychiatric disorders. For example, a recent study of adopted parents in Portugal using descriptive rather than formal psychiatric terms reported a wide range of concerns, of similar form to those reported by birth families (Alves et al, 2022). Similar wide-ranging descriptions of concerns have also been found in UK samples (Meakings et al, 2018) and US samples (Houston & Kramer, 2008; Waid & Alewine, 2018).…”
Section: Introductionmentioning
confidence: 77%
“…Research has also indicated that there may be different levels of need at different points in the adoption journey, but also that the research messages can vary by adoption context. For example, parents in Portugal identified the first few years as especially difficult (Alves et al, 2022) contrasting with research in the US which found needs increased over time (e.g., Waid & Alewine, 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Adoptive parents are faced not only with normative challenges of parenthood but also with unique adoption-related ones (e.g., infertility; birth child losses; late parenthood; abrupt transition to parenthood, child's preexisting behavioral/emotional di culties; stigma regarding adoption; unmet children's expectations) (e.g., Alves et al, 2022;Foli et al, 2017;McKay et al, 2010;Santos-Nunes et al, 2020).…”
Section: Adoptive Versus Non-adoptive Parenthoodmentioning
confidence: 99%
“…However, as depicted in literature, when compared with non-adoptive ones, adoptive parents more easily display irritation, anger, or frustration towards children's negative behavior (Solomon & Poirier, 2005) and more frequently report parent-child relationship problems and associated children's emotional and behavioral di culties (Alves et al, 2022). Due to the unique hardships and stress factors adoptive parents go through preplacement, nurturing adopted children, with a challenging past of their own, in a postplacement setting shaped by these circumstances, can be very psychologically demanding (Chorão et al, 2022;Foli et al, 2017).…”
Section: Adoptive Versus Non-adoptive Parenthoodmentioning
confidence: 99%